2018
DOI: 10.1515/orhu-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

A summary of intentional poisoning of Peregrine Falcons in Switzerland during the last decade

Abstract: In May 2011, a webcam in Zurich, Switzerland, registered the sudden death of a Peregrine Falcon. Analyses revealed that poison had been applied to the nape feathers of the pigeon captured by the bird. This case really raised the awareness of Peregrine Falcon poisoning by pigeon fanciers in Switzerland. BirdLife Switzerland, with the help of numerous partners, started researches on the subject that pigeon fanciers began a “war” against Peregrine Falcons and other raptors. Between 2006 and 2017, BirdLife Switzer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Toxicological analyses of 17 poisoned endangered Eurasian griffons (Gyps fulvus) in Croatia showed the presence of carbofuran in the livers of 15 birds (88%; Muzinic 2007). Inderwildi et al (2018) reported the presence of carbofuran in 50% of poisoned peregrines in Switzerland. A lower frequency of birds with carbofuran (7% of 28 birds) was found by Molenaar et al (2017) in red kites (Milvus milvus) in England.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxicological analyses of 17 poisoned endangered Eurasian griffons (Gyps fulvus) in Croatia showed the presence of carbofuran in the livers of 15 birds (88%; Muzinic 2007). Inderwildi et al (2018) reported the presence of carbofuran in 50% of poisoned peregrines in Switzerland. A lower frequency of birds with carbofuran (7% of 28 birds) was found by Molenaar et al (2017) in red kites (Milvus milvus) in England.…”
Section: Discussionmentioning
confidence: 99%
“…Access to the market of legally purchased pesticides may generate illicit trafficking, which is an increasing problem (Ruiz-Suárez et al 2015, Helou et al 2019, Cuenca et al 2020. Noteworthy is the fact that local communities may collect banned pesticides not only for agricultural purposes, but also to combat non-target species such as wild birds or mammalian predators that are considered to be conflict species, including rare species with high conservation priority (Tennakoon et al 2009, Richards 2012, Chiari et al 2017, Inderwildi et al 2018, Pacheco et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…In Switzerland, in recent years, information has been collated on more than 30 proven or suspected cases of the poisoning of Peregrines typically with baited pigeons (Inderwildi et al . 2018, M. Sinniger pers. comm.).…”
Section: Methodsmentioning
confidence: 99%
“…As Peregrine population evolved, pigeon-fanciers ceased breeding high-flyers in some parts of Hungary. In other areas, they still use illegal methods to eliminate falcons attacking their flocks (Inderwildi et al 2018).…”
Section: Threatsmentioning
confidence: 99%